REVISITING APPROACHES IN HISTORICAL ACCOUNTING STUDIES TOWARDS A RESEARCH AGENDA IN BRAZIL - Alann Inaldo Silva de Sá Bartoluzzio; Nascimento Pedroso, Claudio; Sauerbronn, Fernanda Filgueiras (Advances in Scientific and Applied Accounting, 2022)
Objective: Revisit Brazilian studies in accounting history to propose a research agenda to provide opportunities for knowledge development based on under-researched approaches arising from the international literature. Method: Bibliographic research on some databases mapped to 34 master’s dissertations, 14 doctoral theses, and 114 scientific articles distributed over forty years (1980-2021). Data categorization followed approaches indicated in the international literature, and the analysis reveals trends, gaps, and opportunities. Discussion: Our finds results indicate a continuous trajectory that based on receptivity, a broad focus, and the potential to develop alternative knowledge in accounting. Although some approaches are more explored, for instance the general, institutional and evolutionary history of accounting thought, others still accommodate meaningful opportunities for contributions, such as prosopography, biography and comparative international history, providing opportunities for the development of new research in the field. Contribution: The study provides the first, extensive and full database revealing the advancement of the approaches in Brazilian accounting history. It also brings studies (theses and dissertations), often disregarded in the area, due to restricted journal listings. The results expand knowledge about the potential of different historical approaches still to be developed in Brazil.